11h-14=8h-5

Simple and best practice solution for 11h-14=8h-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11h-14=8h-5 equation:


Simplifying
11h + -14 = 8h + -5

Reorder the terms:
-14 + 11h = 8h + -5

Reorder the terms:
-14 + 11h = -5 + 8h

Solving
-14 + 11h = -5 + 8h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-8h' to each side of the equation.
-14 + 11h + -8h = -5 + 8h + -8h

Combine like terms: 11h + -8h = 3h
-14 + 3h = -5 + 8h + -8h

Combine like terms: 8h + -8h = 0
-14 + 3h = -5 + 0
-14 + 3h = -5

Add '14' to each side of the equation.
-14 + 14 + 3h = -5 + 14

Combine like terms: -14 + 14 = 0
0 + 3h = -5 + 14
3h = -5 + 14

Combine like terms: -5 + 14 = 9
3h = 9

Divide each side by '3'.
h = 3

Simplifying
h = 3

See similar equations:

| -7s=-8s-5 | | 21-9=6n | | 24x-9-16x+2=22x-7-14x+16 | | 8x-18=-30 | | -(6x-3)+6x= | | 3a+9b=30 | | 10x-10-4=3x-27x+20 | | (120+2x)(50+2x)=0 | | 10x-10-4=3x-27x+29 | | 6x+4(x-2)= | | (8x^2+5x-9)+(3x^2+8x)= | | 3(2y-3)=5(y+3) | | -8-h=8-5h | | 3(2y-3)=(y+3) | | N-0.7=3.9 | | 50-5x+5x=50 | | 160-5x=140 | | 6.50h+5=21.25 | | 9-x+35=5 | | -x-1=5x+53 | | 3x-9=21x+3 | | 3.50x=5.25-11 | | x^2-14x-250=0 | | 6+4x=2x+12 | | 71=3x-4 | | 8y+6x=40 | | .7x-2=5.5 | | 7=-2x-3 | | 2x+3(-3)=-1 | | 4x^2-24x+18=0 | | -x+13=4 | | 4x+12=-7 |

Equations solver categories